Preliminary characterization of a novel mitochondrial myopathy mouse model - Yılmaz, Mehmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Mitochondria provide a significant portion of the ATP to cells and govern cellu lar energy economics on ever-changing cellular energy requirements. Cells evolved to monitor mitochondrial stress and developed counteracting stress response mechanisms to counteract mitochondrial dysfunction. Mitochondrial diseases are rare but complex diseases; involvement of both nuclear and mitochondrial genomes, threshold effect, and tissue specific manifestations of the disease increase the conundrum. Neuromuscular involvement in mitochondrial diseases is usually associated with mitochondrial my opathies, which are progressive in nature and may cause premature death. For this study, we generated a novel mitochondrial myopathy mouse model by disrupting the function of the mitochondrial aspartyl-tRNA synthetase gene (Dars2 ) in the skele tal muscle. Mitochondrial aminoacyl-tRNA synthetases are vital for mitochondrial protein translation since they aminoacylate uncharged tRNAs, and their dysfunction hampers mitochondrial translation. In skeletal muscle-specific Dars2 deleted mice, we observed severe and progressive mitochondrial myopathy that causes muscle atrophy and significant reduction in lifespan and body weight. Knockout mice exhibited exer cise intolerance, decreased locomotor activity, and muscle strength compared to their littermates. We detected hypoglycemia and an overall decrease in electron transport chain complexes at the molecular level. On the other hand, various stress responses were evoked in the knockout mice. Terminal stage mice displayed increased mitochon drial biogenesis and mitochondrial integrated stress response in both cell-autonomous and non-autonomous manner. Moreover, an impairment in autophagy and an advanced antioxidant response were observed. Our findings may create windows of opportunity for additional interventions in mitochondrial diseases.
Keywords: Mitochondrial pathology.